2006
DOI: 10.1002/hep.20973
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease: From Steatosis to Cirrhosis

Abstract: Nonalcoholic steatohepatitis (NASH), the lynchpin between steatosis and cirrhosis in the spectrum of nonalcoholic fatty liver disorders (NAFLD), was barely recognized in 1981. NAFLD is now present in 17% to 33% of Americans, has a worldwide distribution, and parallels the frequency of central adiposity, obesity, insulin resistance, metabolic syndrome and type 2 diabetes. NASH could be present in one third of NAFLD cases. Age, activity of steatohepatitis, and established fibrosis predispose to cirrhosis, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

25
1,782
3
48

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,191 publications
(1,889 citation statements)
references
References 162 publications
25
1,782
3
48
Order By: Relevance
“…Some patients with NAFLD develop progressive fibrosis and subsequent cirrhosis with an increased risk of hepatocellular carcinoma 6. The prevalence of cirrhosis among patients with NAFLD is approximately 5%, and patients with NAFLD have an increased mortality compared to control populations 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients with NAFLD develop progressive fibrosis and subsequent cirrhosis with an increased risk of hepatocellular carcinoma 6. The prevalence of cirrhosis among patients with NAFLD is approximately 5%, and patients with NAFLD have an increased mortality compared to control populations 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Once steatosis is present, the liver becomes more susceptible to the "second-hit"; oxidative/nitrosative/nitrative stress, which is thought to be one of several stimuli for the progression from simple fatty liver to ASH or NASH. The molecular mechanism underlying how steatosis predisposes liver to transition from simple fatty liver to steatohepatitis is not clear; however, several studies point to the possibility that when hepatocytes accumulate fat the fatty acids themselves are toxic and initiate a pathological response called "lipotoxicity" [14]. Studies show that free fatty acids are toxic to hepatocytes via deregulation of lysosomal metabolism [15,16] and induction of endoplasmic reticulum stress [17,18] resulting in apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, reduced survival and higher mortality from cardiovascular and liver‐related causes have been reported among NASH patients in comparison with a reference population 4 . Several factors, including body mass index (BMI), age, hyperglycemia, dyslipidemia and hypertension, have been linked to the severity of NAFLD 5 , and the presence of diabetes, in particular, has received a great deal of attention. One previous study found that type 2 diabetes was an independent predictor of progression to fibrosis in NASH patients 6 , and the histological data of 458 Italian NAFLD patients showed that NASH was independently predicted by diabetes 7 .…”
Section: Introductionmentioning
confidence: 99%